Analisis Faktor Penyebab Anak Putus Sekolah di RT. 01 dan RT. 02 Kelurahan Kasang Kecamatan Jambi Timur - Saputra, Lucky; Sari, Pratiwi Indah (Universitas Batanghari Jambi, 2025)
This research aims to determine the causes of children dropping out of school in RT. 01 and RT. 02 Kasang Village, East Jambi District. The research method used in this research is a qualitative method. The research results show the factors that cause children to drop out of school in RT. 01 and RT. 02 Kasang Village, East Jambi District. namely, family economic causes that cause children to drop out of school, lack of parental attention that causes children to drop out of school, and family environment. However, analytically it can be clearly seen that family economic factors dominate the causes of dropping out of school among children in RT. 01 and RT. 02 Kasang Village, East Jambi District.